Hocus-pocus hound - Hay, Samantha; Reed, Nathan (London : Kingfisher, 2008)
Marvo the magician replaces his assistant, Doris, with Hocus-Pocus Hound, with some surprising results.
3.6
K-3.
K-3
Keywords: Dogs -- Fiction; Magicians -- Fiction; Dogs -- Fiction; Magicians -- Fiction